LSTM Neural Network for Inferring Conduction Velocity Distribution in Demyelinating Neuropathies - Nodera, Hiroyuki; Matsui, Makoto (Frontiers in Neurology, 2021)
Waveform analysis of compound muscle action potential (CMAP) is important in detailed analysis of conduction velocities of each axon, as seen in temporal dispersion. This understanding is limited because conduction velocity distribution cannot be easily available from a CMAP waveform. Given the recent advent of artificial intelligence, this study aimed to assess whether conduction velocity (CV) distribution can be inferred from CMAP by use of deep learning algorithms. Simulated CMAP waveforms were constructed from a single motor unit potential and randomly created CV histograms (n = 12,000). After training the data with various recurrent neural networks (RNNs), CV inference was tested by the network. Among simple RNNs, long short-term memory (LSTM), and gated recurrent unit (GRU), the best accuracy and loss profiles were shown by bidirectional two-layer (LSTM), with training and validation accuracies of 0.954 and 0.975, respectively. Training with use of a recurrent neural network can accurately infer conduction velocity distribution in a wide variety of simulated demyelinating neuropathies. Using deep learning techniques, CV distribution can be assessed in a non-invasive manner.